Rosácea eritêmato-telangiectásica e risco cardiovascular: avaliação do efluxo de colesterol mediado pela Lipoproteína de Densidade Alta (HDL) - Trivelin, Maria Laura de Oliveira de Avelar Alchorne (2021)
Inflammation plays an important role in the pathogenesis of rosacea and is a prominent factor in the development of atherosclerosis and its complications. The higher prevalence of cardiovascular disease was demonstrated in rosacea, although there is still no consensus in the literature since in many studies the adjustment for cardiovascular risk factors abolishes the association between rosacea and cardiovascular outcomes. High-density lipoprotein (HDL) removes cholesterol from macrophages, despite HDL cholesterol and apolipoprotein A-I plasma concentrations, may be compromised in inflammatory conditions, increasing cardiovascular risk. The aim of the present study is to evaluate, in subjects with erythematotelangiectatic rosacea, the profile of plasma lipids, cardiovascular risk and macrophage cholesterol removal. Subjects with rosacea (n = 41), of both sexes, were recruited at the Dermatology Clinic of Universidade Nove de Julho and matched, by sex and age, with control subjects (n = 41). Anthropometric data were obtained from all individuals. Venous blood was collected, after 12 hours of fasting and plasma isolated for lipid and apolipoprotein measurements, by enzymatic and immunoturbidimetry methods. Serum was depleted in apolipoprotein B, by incubation with dextran sulfate/magnesium chloride, and used as a cholesterol acceptor from macrophages previously overloaded with acetylated LDL and 14C-cholesterol. Mean disease duration was 1 to 10 years in 73% of individuals with rosacea, with the disease predominantly on the face. Most individuals (76%) were not undergoing any type of treatment. The control and rosacea groups were similar in BMI distribution, waist circumference, smoking prevalence, alcohol consumption, menopausal status, plasma lipid and apolipoprotein profile, and atherogenic indices. Only systolic and diastolic blood pressure was lower in the rosacea group. The efflux of 14C-cholesterol from macrophages, mediated by apoB-depleted serum, was similar between individuals in the control (8.3%) and rosacea (8.2%) groups. In conclusion, in individuals with erythematotelangiectatic rosacea, matched with controls regarding the main cardiovascular risk factors, no alterations were observed in the removal of cholesterol from macrophages by HDLs. This finding shows that the first stage of reverse cholesterol transport is preserved, not constituting an aggravation of cardiovascular risk in this disease.